Antihyperglycemic Effects of Aqueous Extracts of Zingiber Officinale, Cinnamonum Zeylanicum and their Combination in Experimental Rats - Usman, Muhammad Ibrahim; Alhassan, Adamu Jibrin; Saיad, Hauwa (The International Journal of Biotechnology, 2018)
This research was conducted to evaluate antihyperglycemic property of aqueous extract of Cinnamon (Cinnamonum zeylanicum) bark; Ginger (Zingiber officinale) rhizome and a combination of the two on Alloxan induced diabetic rats. Thirty two rats were grouped into eight groups of four rats each. Group I served as normal control, group II were normal rats and administered with 200mg/kg body weight of ginger aqueous extract, group III were normal rats and administered with 150mg/kg body weight of Cinnamon aqueous extract. Group IV served as diabetic control group, group V were diabetic and administered with 200mg/kg body weight of ginger extract, group VI were diabetic and administered with 150mg/kg body weight of Cinnamon extract. Group VII were diabetic and administered with a combination of Ginger and Cinnamon extract in a ratio of 4:3 respectively. Group VIII were diabetic and administered with metformin at a dose of 500mg/kg body weight. The animals were administered with the extracts for 14 days while monitoring the fasting blood glucose at a 3-day intervals. The fasting blood glucose level was found to be significantly (p<0.05) decreased in all groups administered with the extracts, with the highest hypoglycemic activity seen in group VII administered with a combination of the two extract compared to the diabetic control group. The findings of this study suggests that Ginger rhizome, cinnamon bark and their combination may be used in the management of diabetes mellitus, although further studies need to be carried to confirm their potential benefits in diabetes management.